Investment Contracts and Foreign Direct Investment: A Juridical Perspective - Moch. Teguh Al Baisar (Journal of Ius Comparatum Law Studies, 2025)
This research investigates the legal framework governing investment contracts and foreign direct investment (FDI) in Indonesia using a normative juridical approach that emphasizes statutory analysis and literature review. The inquiry is grounded in primary legal materials, including the Indonesian Civil Code (KUHPerdata) and Law Number 25 of 2007 concerning Investment, and is further enriched by secondary and tertiary materials to provide a broader context of the regulatory landscape. The study delves into the nature of investment contracts as instruments that create legal certainty, delineate rights and obligations, and ensure the fulfillment of commitments by the parties involved throughout the investment process. It emphasizes that investment contracts must fulfill the essential elements of a valid agreement as stipulated in Article 1320 of the Civil Code and are binding under the principle of pacta sunt servanda. Moreover, the analysis explores the interplay between investment contracts and various FDI structures, particularly joint ventures (PT PMA), as required by Indonesian law. It highlights key contractual components—such as capital participation, management rights, profit repatriation, stabilization clauses, and choice of law—that enhance clarity and predictability for investors while respecting the regulatory authority of the host state. The findings underscore the importance of a well-drafted investment contract in minimizing legal uncertainty, facilitating technology transfer, and promoting sustainable economic growth, which ultimately strengthens Indonesia’s appeal as a destination for foreign investment.